Maternal gut microbiome–induced IgG regulates neonatal gut microbiome and immunity - Katherine Z. Sanidad; Mohammed Amir; Aparna Ananthanarayanan; Anvita Singaraju; Nicholas B. Shiland; Hanna S. Hong; Nobuhiko Kamada; Naohiro Inohara; Gabriel Núñez; Melody Y. Zeng (2022)
The gut microbiome elicits antigen-specific immunoglobulin G (IgG) at steady state that cross-reacts to pathogens to confer protection against systemic infection. The role of gut microbiome–specific IgG antibodies in the development of the gut microbiome and immunity against enteric pathogens in early life, however, remains largely undefined. In this study, we show that gut microbiome–induced maternal IgG is transferred to the neonatal intestine through maternal milk via the neonatal Fc receptor and directly inhibits Citrobacter rodentium colonization and attachment to the mucosa. Enhanced neonatal immunity against oral C. rodentium infection was observed after maternal immunization with a gut microbiome–derived IgG antigen, outer membrane protein A, or induction of IgG-inducing gut bacteria. Furthermore, by generating a gene-targeted mouse model with complete IgG deficiency, we demonstrate that IgG knockout neonates are more susceptible to C. rodentium infection and exhibit alterations of the gut microbiome that promote differentiation of interleukin-17A–producing γδ T cells in the intestine, which persist into adulthood and contribute to increased disease severity in a dextran sulfate sodium–induced mouse model of colitis. Together, our studies have defined a critical role for maternal gut microbiome–specific IgG antibodies in promoting immunity against enteric pathogens and shaping the development of the gut microbiome and immune cells in early life.